The syntax of Merap phrases, clauses and sentences. A Study Based on Government and Binding, Principles and Parameters Approach - Radjaban, Yohanes; Humanika, Eko Setyo; Hariyanti, Tatit (Technium Social Sciences Journal, 2022)
This research is to describe (1) linguistic typology, (2) phrase structures, (3) clause and sentence structures of Merap language. The analyses on the problems apply Principles & Parameters approach to come to the findings. Historical generative method was applied to verify the linguistic typology of Merap and Parameters and Principles of Haegeman’s Government and Binding Theories were applied to describe phrase structures, clause, and sentence structures of Merap. Based on the analyses, the research formulated some findings. First, Merap language is a sub-Kayanic language. Second, the structures of phrases of Merap are constructed based on head-modifiers relations with a category as a head and the other elements as modifiers. Third, clause structures of Merap are constructed based on head-modifier relations with a verb as a head and with NP, AdvP, PP, and AP as modifiers, and sentence structures of Merap are constructed based on head-modifier relations with a complementizer as a head and an IP as its modifier. Key words: syntax; Merap; head-modifier relations; complementizer